Multi-faceted nutritional interventions are imperative to reduction of stunting among children in low- and middle-income countries - Sharn, Amy R.; Oliveros, Elena; Lai, Stephanie; Sanchez, Claudia P.; Villa-Real Guno, Mary Jean; Rojas Montenegro, Clara (Frontiers in Nutrition, 2025)
Worldwide, 1 in 5 children under 5 years experiences undernutrition; most commonly in in low- and middle-income countries. Inadequate nutrient and energy intake places children at risk of stunted growth, which is associated with delayed development, increased mortality, and reduced productivity in adulthood. We investigated global approaches for managing stunting in young children (ages 1–5 years) by reviewing research on nutrition-focused interventions and public health frameworks. Our aim was to identify components of effective nutritional care and monitoring. We screened 1,636 studies, reviewed 207 abstracts and full-texts, and included 9 studies for final analysis. These studies, conducted in China, Colombia, Guatemala, Haiti, India, Mexico (n = 2), Peru, and Vietnam evaluated clinical outcomes such as anthropometrics and dietary intake. Most interventions included caregiver nutrition education (n = 7), but none used routine and frequent nutrition screening; only 4 included frequent follow-ups, 3 assessed breastfeeding frequency, and 4 used macronutrient and micronutrient supplementation when indicated. Economic outcomes were reported in 4 studies, while process and clinical outcomes were commonly reported (n = 7). Based on our review, effecting stunting interventions should include: (i) routine screening of every child for nutritional risk based on WHO and UNICEF guidance, (ii) caregiver-targeted nutrition education (iii) supplementation with macro- and micronutrients as needed, and (iv) regular follow-up to monitor growth and nutritional status. Although the evidence base was small, stringent inclusion criteria focused on community-based, multi-component interventions. This highlights the need for expanded implementation research, particularly in under resourced regions. Comprehensive, multi-level strategies are essential to address the long-term health risks of pediatric undernutrition.